2014
DOI: 10.1111/imr.12146
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory triggers of acute rejection of organ allografts

Abstract: Summary Solid organ transplantation is a vital therapy for end stage diseases. Decades of research has established that the components of the adaptive immune system are critical for transplant rejection, but the role of the innate immune system in organ transplantation is just emerging. Accumulating evidence indicates that the innate immune system is activated at the time of organ implantation by the release of endogenous inflammatory triggers. This review discusses the nature of these triggers in organ transp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(88 citation statements)
references
References 118 publications
2
84
0
Order By: Relevance
“…23,37,53 We suggest that suppressing the inflammatory response may well facilitate the role of the immunosuppressive therapy and reduce the risk of both rejection and coagulation dysfunction. [54][55][56] We have data suggesting that the cytokine, interleukin-6 (IL-6), is playing a role and that IL-6R blockade reduces this response. 23 IL-6R blockade does not have an inhibitory effect on platelet aggregation in vitro (H. Iwase unpublished data).…”
mentioning
confidence: 99%
“…23,37,53 We suggest that suppressing the inflammatory response may well facilitate the role of the immunosuppressive therapy and reduce the risk of both rejection and coagulation dysfunction. [54][55][56] We have data suggesting that the cytokine, interleukin-6 (IL-6), is playing a role and that IL-6R blockade reduces this response. 23 IL-6R blockade does not have an inhibitory effect on platelet aggregation in vitro (H. Iwase unpublished data).…”
mentioning
confidence: 99%
“…34 Our data showed that the phosphorylation of NFκB-p65 was significantly increased in DCD allografts with low-dose tacrolimus compared to the CIT-only control. 34 Our data showed that the phosphorylation of NFκB-p65 was significantly increased in DCD allografts with low-dose tacrolimus compared to the CIT-only control.…”
Section: High Immunosuppression Reduced Apoptosis In the Renal Allomentioning
confidence: 51%
“…It has been shown that the inflammatory cytokines produced in IRI may enhance the adaptive immune response to the allograft after transplantation. 34,35 Therefore, we investigated the activation of Our data showed that the phosphorylation of NFκB-p65 was significantly increased in DCD allografts with low-dose tacrolimus compared to the CIT-only control. Phosphorylated NFκB-p65 has been associated with the inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines are assumed to be present at time 0 since transplantation is associated with surgical trauma and exposure to bacterial and viral agents. Additionally, during the procedure, the reconnection to the recipient circulation initiates the process of ischemia/reperfusion injury, causing rapid accumulation of inflammatory mediators (31, 42, 43). Although there is a general agreement on the presence of inflammatory elements at time 0, the overall amount is not known and, thus, an arbitrary value is chosen here.…”
Section: Methodsmentioning
confidence: 99%